A Cross Sectional Study on Health Seeking Behaviour among Elderly in Shimoga - Nandini C; Saranya R (Medsci Publications, 2019)
Background: According to Census 2011 nearly 104 million elderly persons in India.6 The 2011 census reveals that Karnataka has 7.9% elderly population. Health seeking behaviours are influenced by a variety of factors among elderly like socioeconomic conditions, age, social status of the person, gender, authority of the elderly within the family. The objective of the study was to assess the health seeking behaviour among elderly in rural and urban field practice areas of Shimoga institute of medical sciences, shimoga Methods: A community-based cross-sectional study was conducted in the urban and rural areas of Shimoga district; the study period was from August 2017 to January 2018. Provisional diagnosis of diseases of elderly was made based on reported symptoms, clinical evaluation by investigators. The data was collected through predesigned and pretested personal interviews by house-to-house visits after taking informed consent from the participants. The data collected were compiled and entered into Microsoft Excel software. For statistical analysis, SPSS version 21 was used. Results: Health seeking behaviors are influenced by a variety of factors among elderly like socioeconomic conditions, age, social status of the person, gender, authority of the elderly within the family. Type of health facility preferred by elderly was government hospital (94.3%) in rural and private hospitals in urban (58.1%) Conclusion: Health and treatment seeking behaviour among elderly is very poor, which needs a awareness creation and creating easy accessibility of health services. It needs implementation of programs at grass root level.